'I Myself Gave Them Laws That Were Not Good': Ezekiel 20 and the Exodus Traditions - Carvalho, Corrine 1958- (1996)
While the book of Ezekiel contains little reflex to the exodus traditions, on closer look it becomes clear that Ezekiel knew some of these traditions. Nowhere is this more apparent than in ch. 20, which culminates in God's declaration that he had given Israel 'no good laws' in order to lead them further into sin. This text functions in the book in two ways. First, as a reaction to the fall of Jerusalem, it preserves the power of God, even at the expense of God's justice. Secondly, it prepares the reader for the new laws revealed to Ezekiel in chs. 40-48.